2017
DOI: 10.3748/wjg.v23.i27.4920
|View full text |Cite
|
Sign up to set email alerts
|

Anti-oxidant and anti-inflammatory effects of hydrogen-rich water alleviate ethanol-induced fatty liver in mice

Abstract: AIMTo investigate the effects of hydrogen-rich water (HRW) treatment on prevention of ethanol (EtOH)-induced early fatty liver in mice.METHODSIn vitro reduction of hydrogen peroxide by HRW was determined with a chemiluminescence system. Female mice were randomly divided into five groups: control, EtOH, EtOH + silymarin, EtOH + HRW and EtOH + silymarin + HRW. Each group was fed a Lieber-DeCarli liquid diet containing EtOH or isocaloric maltose dextrin (control diet). Silymarin was used as a positive control to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 53 publications
1
27
0
Order By: Relevance
“…Molecular hydrogen has been shown to have a protective role in liver function in liver disease, as evidenced by the decreased ALT, AST or TBA levels 17 19 in serum. The decline in these parameters were also observed in our study, although ALT was not significantly altered in HRW group.…”
Section: Discussionmentioning
confidence: 99%
“…Molecular hydrogen has been shown to have a protective role in liver function in liver disease, as evidenced by the decreased ALT, AST or TBA levels 17 19 in serum. The decline in these parameters were also observed in our study, although ALT was not significantly altered in HRW group.…”
Section: Discussionmentioning
confidence: 99%
“…This is the first time that an in vivo mouse model (BALB- neu T) is used to show the direct effects of ERW on cancer. Previous in vivo studies with ERW focused on other factors: nephroprotective effect of ERW against cisplatin-induced kidney toxicity and oxidative damage in mice [ 42 ] and antioxidant and anti-inflammatory effects of hydrogen-rich water in alleviating ethanol-induced fatty liver in mice [ 67 ]. Our in vivo study showed that BALB- neu T mice that drank ERW delayed the development of tumors compared to the control.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the interplay between oxidative stress and inflammation in ethanol-induced liver damage has been discussed by multiple studies [ 64 66 ]. Oxidative stress can trigger the expressions of proinflammatory proteins to facilitate inflammatory responses, of which NF- κ B activation is involved [ 67 72 ].…”
Section: Discussionmentioning
confidence: 99%